Development of a thermal-radiation single-drum roll dryer for concentrated food stuff - Cherevko, Oleksander; Mikhaylov , Valeriy; Zahorulko , Andrii; Zagorulko , Aleksey; Gordienko , Irina (Eastern-European Journal of Enterprise Technologies, 2021)
The design of a thermal-radiation single-drum roll dryer with a combined method of heat supply, application and cutting of the dried layer of raw materials was developed. The dryer allows obtaining a powder fraction of a semi-finished product with a solids content of 3...5 %. Such a design solution will make it possible to obtain a high-quality semi-finished product due to low-temperature drying. The effective viscosity of the studied pastes produced by blending apple, sea buckthorn, black chokeberry, beet and pumpkin purees was determined. Adding different percentages of raw materials to apple paste increases the effective viscosity by 9...18 %. According to the results of the organoleptic evaluation, the sample with the following composition turned out to be the best: apple – 30 %, sea buckthorn – 20 %, black chokeberry – 15 %, beet – 15 % and pumpkin – 20 %. The drying time of the blended paste with a solids content of 45 % at a temperature of 65 °C and different layer thicknesses of application to the working surface (8, 6 and 4 mm) is 75, 60 and 56 min, respectively. All the samples of pastes have a reddish-purple color with a wavelength of 610.5...614.5 nm and a tone purity of 66.5...78.8 %. The wavelength of the dried fraction is 495...615.3 nm with a tone purity of 34.3...34.8 %, from bluish-red to bluish-purple. The brightness of the samples after drying decreases within 3...4 %. The obtained color change values and drying time of the samples confirm the possibility of using the improved dryer to obtain high-quality vegetable semi-finished products of the dried fraction. The experimental data will be useful in design calculations and testing of the developed dryer in order to obtain its maximum efficiency